Youth Lived Experiences in High-Rise Housing: Implications for Health and Urban Planning - Chan, Matthew (University of Waterloo, 2026)
Continued global urbanization and the growth of high-rise residential development have increasingly shaped the environments in which young people live. Although related areas of study have examined how built, natural, and social environments influence youth well-being, the health implications of high-rise living for youth remain poorly understood. In the present study, small semi-structured focus groups (2-4 participants) with 19 youths aged 13-18 were conducted, lasting between 63 and 86 minutes. Each focus group was recorded, transcribed, and analyzed using the Framework Method to identify recurring themes. Five themes were developed: Safety and Security; Public Space Design and Accessibility; Social Inclusion and Participation; Economic and Structural Barriers to Youth Needs; and Physical and Mental Health. Youth described both positive and negative experiences within high-rise and high-density environments, associated features such as clean public spaces, social infrastructure, and recreation areas with positive well-being; whereas they identified homelessness, drug use, and poor lighting negatively, which led to avoidance of certain public spaces. A central theme that emerged from the data was youth perceptions of safety and social disorder, indicating that challenges in high-rise environments extend beyond planning and design but also relate to social and environmental conditions. The study contributes to understanding how youth experiences can inform more inclusive and healthier high-rise urban environments.
Keywords: youth; health; high-rise; planning; urbanization